The affective commitment of newcomers in hybrid work contexts: A study on enhancing and inhibiting factors and the mediating role of newcomer adjustment - Mazzei, Alessandra; Ravazzani, Silvia; Butera, Alfonsa; Conti, Sara; Fisichella, Chiara (Frontiers in Psychology, 2023)
This study focuses on one of the most impacted human aspects of digital transformation in contemporary organizations: the development of affective commitment of newcomers in hybrid work contexts. Specifically, this study addresses a research gap related to the factors that influence affective commitment of newcomers in hybrid work contexts. First, it investigates the role of two drawbacks of the remote component of hybrid work contexts inhibiting affective commitment: workplace social isolation and technostress. Second, it explores the role of two factors previously investigated in in-presence contexts and enhancing affective commitment: perceived organizational support and perceived supervisor support. Moreover, this study considers the possible mediating role of newcomer adjustment, intended as a proximal outcome of a successful onboarding and an antecedent of newcomer affective commitment. In order to examine enhancing and inhibiting factors and the mediating role of newcomer adjustment, a quantitative study was carried out involving newcomers that began to work in their current organization after January 2021 and that still work in remote working at least one day a week. Results confirm the inhibiting role of workplace social isolation and the enhancing role of perceived organizational support and perceived supervisor support on affective commitment in hybrid work contexts. Furthermore, they support the mediating role of newcomer adjustment in the relationship between workplace social isolation and affective commitment. While contributing to theory advancement in understanding newcomer affective commitment in current hybrid work contexts, these results also suggest important managerial implications in the field of human resources management, specifically the need to pay greater attention to strategies devoted to increasing newcomers’ perception of organizational and supervisor support.